Active vibration control in building-like structures submitted to earthquakes using multiple positive position feedback and sliding modes (2014)
This work deals with the structural and dynamic analysis of a building-like structure consisting of a three-story building with one passive/active vibration absorber. The base of the structure is perturbed using a shaker, providing excitation forces and noisy excitations emulating ground transportation, underground railways and earthquakes, quite common in Mexico City. It is considered a realistic seismic record of 8.1Mw occurred at Mexico City, containing some resonant frequencies of the structure. The mechanical structure is modeled using Euler-Lagrange methodology and validated using experimental modal analysis techniques. The active control scheme is synthesized to actively attenuate the noise and vibration system response, caused by noisy excitation forces acting on the base, by employing Multiple Positive Position Feedback and Sliding Mode Control to improve the closed-loop system response and, simultaneously, attenuate three vibration modes. Simulation and experimental results describe the overall system performance.